Weekend-Based Parent-Group Intervention to Reduce Stress in Parents of Children and Adolescents with Type 1 Diabetes: A Pilot Study. (29th November 2019) - Ferrito, Lucia; Predieri, Barbara; Pjetraj, Dorina; Alessandrelli, Maria Cristina; Pagnini, Manuela; Iannilli, Antonio; Marino, Monica; Tombolini, Stefano; Pintaudi, Basilio; Lucisano, Giuseppe; Zani, Fabiana; Iughetti, Lorenzo; et al.
Abstract : Diagnosis of type 1 diabetes (T1D) in a child is often associated with anger, denial, fear, and depression from the parents. The aim of the study was to improve parents' adaptation to the diagnosis of diabetes of their child. Sixty-two parents (29 mothers, 33 fathers) of 36 children with type 1 diabetes (mean   age = 11.3 ‐ 3.3   years ; diabetes   duration > 1   year ; HbA 1 c = 57 ± 11   mmol / mol ) participated in a three-day educational working group pilot intervention study. Intervention was based on the reexamination of the traumatic event of diagnosis of T1D through spatial and time-line anchorage, retracing of the future, emotional awareness, and interactive discussion. Relaxing technique, diaphragmatic breathing, and guided visualization were used by 2 psychologists and 1 pediatric endocrinologist. The study was approved by EC and participants filled a consent form. At baseline and after intervention, parents filled in a questionnaire including Diabetes-Related Distress (DRD), Parent Health Locus of Control Scale (PHLOC), Parent Stress Index Short Form (PSI-SF), Hypoglycemia Fear Survey-Parents (HFS-P) and Hypoglycemia Fear Survey-Parents of Young Children (HFS-P-YC), and Health Survey Short Form-36 (SF-36). Three months after the intervention, both parents reported a reduction in the "difficult child" subscale of the PSI-SF (p < 0.05 ) and increased scores of social functioning of the SF-36 (p < 0.05 ). DRD score was significantly reduced in mothers (p = 0.03 ), while the "parental distress" subscale of the PSI-SF was significantly improved in fathers (p = 0.03 ). This weekend-based parent group intervention seems to reduce stress and improve social functioning of parents of children and adolescents with type 1 diabetes.